The influence of e-portfolio toward the process and the quality of students' translation - Maya Rahmawati; Putri Kamalia Hakim (Journal on English as a Foreign Language, 2018)
This study is aimed at gaining an understanding of the influence of e-portfolio on the process and quality of translation (acceptability, accuracy, and readability) of students and how e-portfolio affects the process and quality of student translations. The method used in this research is sequential explanatory design. The subjects of this study are the third-year students of English Education Department at Universitas Singaperbangsa Karawang (UNSIKA) Indonesia who took translation practice course. The quantitative data are taken from the pre-test and post-test results. The qualitative data are gained from questionnaire and interview. After analysis, it is found that e-portfolio influenced the students’ translation ability where the value is Sig. = 0.001 < α = 0.05. It was discovered that 82% students achieved higher score in acceptability. Meanwhile, 62% students achieved higher score in accuracy, and only 56% students achieved higher score in readability. In terms of translation process, e-portfolio helps students track their progress, give and receive feedback from various participants, as well as have virtual room to sort their works which are easily accessible.